2018
DOI: 10.3390/su10092963
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Socio-Psychological Factors on Actual Adoption of Sustainable Land Management Practices in Dryland and Water Stressed Areas

Abstract: Despite the presence of several studies on technology adoption, there are limited empirical studies on how socio-psychological factors affect the adoption of sustainable agriculture. Therefore, this paper investigates how socio-psychological factors-such as social capital, information, attitudes, efficacy, and aversion-affect smallholder farmers’ decisions to adopt sustainable land management practices, such as agroforestry systems, organic compost, and crop rotation with legumes. Cross-sectional data are coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 40 publications
5
35
2
Order By: Relevance
“…The coefficient for technology attitude was negative and significant at the 10% level, suggesting that the litchi farmers who were more eager to apply new technology were more likely to apply the top grafting technique. This result supports the possibility that the attitude toward technology leads to a practical technique uptake [14,27].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The coefficient for technology attitude was negative and significant at the 10% level, suggesting that the litchi farmers who were more eager to apply new technology were more likely to apply the top grafting technique. This result supports the possibility that the attitude toward technology leads to a practical technique uptake [14,27].…”
Section: Resultssupporting
confidence: 80%
“…However, some studies have found that larger farm sizes and a higher percentage of family income coming from the farm have a negative or insignificant effect on technology adoption. This is normally explained by their risk tolerance level [14].…”
Section: Variable Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of influence of physical effects on the willingness of farmers could be attributed to the limited direct biophysical benefits of the program to most individual households since the intervention has been mainly confined to selected micro-watersheds on communal lands both in Ararso-Bero and Sara-Areda. This is consistent with other studies in Ethiopia that indicate that farmers are less motivated to participate in an initiative [34] or adopt conservation technologies [35,36] that will not generate short-term benefits at a farm household level. In addition, in some micro-watersheds, SWC structures and planted tree seedlings were being destroyed by flood water coming down from upstream neighboring Kebeles, particularly in Ararso-Bero and Qachachule-Guja.…”
Section: Outcome Scoressupporting
confidence: 91%
“…Some studies on the economics of sustainable land management have suggested incentives for farmers to adopt sustainable land management practices based on the analysis of their household characteristics as well as the features and attributes of their farm operations (Semgalawe, 1998;Namboth, 2015;Menozzi et al, 2015;Saguye, 2017a;Zeweld et al, 2018;Meijer et al, 2014;Vo et al, 2018;Wang et al, 2018). According to Tenge et al (2004) and Bravo-Ureta et al (2006), the analyses to determine the factors affecting land degradation often focus exclusively on characteristics at household level, including the socio-economic characteristics of the farmers (age, gender, level of education, etc.…”
Section: Introductionmentioning
confidence: 99%